The effects of process parameters on concentration of pineapple fruit juice via freeze concentration technique - Mohd Hasrul, Yaakob (2012)
Freeze concentration of fruit juices is a method of removing water from juices without heating and changing juice flavor. Freeze concentration is effective because a solute in solution has a lower melting point than pure ice and can be separated from the water component(ice)as the temperature approaches the melting point of pure ice.In addition,the advantage of the freeze concentration technique is based on the quality of the product obtained due to the low temperatures used in the process,which makes it a very suitable technology for the processing of fruit juices. The objective of this research is to study the effects of process parameters on concentration of pineapple fruit juice via freeze concentration technique.By using crystallizer unit, different parameters were studied to find the optimum concentration:temperatures and stirring rate.The first part of this experiment will be conducted to determine the best concentration of pineapple juice stirring rate and at temperature of -16°C.The stirring rate will be varied at 200 rpm, 600 rpm, 1000 rpm, 1400 rpm and 1800 rpm.For every 1 hour, the concentration of juice will be checked. The experiment will be conducted for 12 hours. Then, the second part will be conducted to determine the effect of temperature at constant stirring rate. The temperature will be verified at 0°C, -4°C, -8°C, -12°C and -16°C.The stirring rate used for this part is -16°C based on the highest concentration results obtained in part one.The concentrated juice will be determined vitamin C content by using HPLC and the concentration using refractometer in °Brix.It was found that the processing condition with -18°C cooling medium and 1800 rpm stirring rate was the best among all studied conditions.